2014
DOI: 10.1063/1.4901507
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of electric-powered taxis: A cross national study

Abstract: Articles you may be interested inAn efficient wireless power transfer system with security considerations for electric vehicle applicationsWith rapidly increasing interest in several significant environmental and transportation issues, namely, greenhouse gas emissions, there have been several attempts to transition the current transportation systems and vehicles to more environment-friendly vehicles. Following this trend, this study aimed to investigate drivers' motivations for adopting electric-powered taxis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Aiginger and Vogel (2015), and (Moore and Benbasat, 1991) pointed out that both actual cost and intangible efforts play notable roles in determining the acceptance of newly introduced technologies and systems. Moreover, Park, Kim, Han, Kwon, Yoo and Ohm (2014) found that perceived cost of a new innovative product or technology should be considered as one of the biggest barriers to adoption of the product or technology.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Aiginger and Vogel (2015), and (Moore and Benbasat, 1991) pointed out that both actual cost and intangible efforts play notable roles in determining the acceptance of newly introduced technologies and systems. Moreover, Park, Kim, Han, Kwon, Yoo and Ohm (2014) found that perceived cost of a new innovative product or technology should be considered as one of the biggest barriers to adoption of the product or technology.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Currently, there are 18,163 taxis in Hong Kong [18]. Taxi companies have also been among the first in the automobile industry to embrace EVs broadly [19]. An illustrative example is the BYD e6 electric cross-over sedan taxis that launched in Hong Kong in 2013 [20].…”
Section: Electric Vehicle Developmentmentioning
confidence: 99%
“…Colombia detected that its automotive park has potential for improvement to contribute to the 20% reduction in polluting emissions by 2030, according to the United Nations Conference on Climate Change (La República, 2018), because the average age of vehicles in Colombia is approximately 16 years according (Crist, 2012) Paris Subsidy of $5,645.48 USD for electric vehicle purchase South Korea (Park et al, 2014) -50% discount allowance for electric taxi purchases from taxi service providers USA (Park et al, 2014) -Subsidy of $7,500 USD for purchase of electric vehicles Subsidies for the installation of Wallbox for electric vehicle buyers China (Yang et al, 2018)…”
Section: Electric Mobility In Colombiamentioning
confidence: 99%